The Harapan Jaya Cooperative Development Reviewed from the Cooperative Financial Capital and Business - Thoharudin, Munawar; Huda, Fatkhan Amirul; Suryadi, Tedi (Journal of Economic Education, 2020)
The purpose of this study was to find out how the Harapan Jaya Cooperative development in terms of cooperative financial capital and business. In financial capital, there are assets, incomes, and Net Income. While the business is from the business run by the cooperative. This study uses a qualitative descriptive method. In this study, the researcher acts as a data collector and as an active instrument to collect data. This research uses two data sources; they are primary and secondary data. Data collection was conducted by researchers using in-depth interviews, documentation and observation. Data analyzed using qualitative analysis, the validity of the data using the triangulation method. The Harapan Jaya Cooperative Capital development in this study was reviewed from the Solvency, Liquidity and Profitability Ratio. Overall shows good and excellent criteria. The development of the cooperative business is indicated by the addition of income from savings and loan units, management of plasma tubers, dump truck rental, beko heavy equipment rental, motor grader heavy equipment. In addition, business development is also seen from the addition of dump trucks and heavy equipment owned by cooperatives.